2013
DOI: 10.1136/oemed-2013-101571
|View full text |Cite
|
Sign up to set email alerts
|

Absence from work and return to work in people with back pain: a systematic review and meta-analysis

Abstract: BackgroundA considerable proportion of work absence is attributed to back pain, however prospective studies in working populations with back pain are variable in setting and design, and a quantitative summary of current evidence is lacking.ObjectiveTo investigate the extent to which differences in setting, country, sampling procedures and methods for data collection are responsible for variation in estimates of work absence and return to work.MethodsSystematic searches of seven bibliographic databases. Inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
78
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(93 citation statements)
references
References 58 publications
2
78
0
2
Order By: Relevance
“…6 No assessment of the subpopulation of people with chronic low back pain (CLBP) has been adequately performed, although several studies have emphasized that EI should be implemented to ensure early return to work (RTW). 7,8 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 No assessment of the subpopulation of people with chronic low back pain (CLBP) has been adequately performed, although several studies have emphasized that EI should be implemented to ensure early return to work (RTW). 7,8 …”
mentioning
confidence: 99%
“…7,9 Therefore, it is important to reduce the length of sick leave. In this study, we sought to examine if EI for people with CLBP would lead to an early RTW and minimize sick leave during 12 months of follow-up compared with patients on a 3-month waiting list (WL).…”
mentioning
confidence: 99%
“…Wynn-Jones et al 1 performed a meta-analysis of studies that followed patients with back pain and assessed if they were absent from work and, if so, for how long. They found that back pain occurs in about 15% of all patients and that 68% of these returned to work within 1 month.…”
mentioning
confidence: 99%
“…Some researchers have tried to standardise the amount of sick leave days per disease as to indicate when an intervention would be needed but it has not become a very popular method. Wynne-Jones et al 1 propose to use an admittedly arbitrarily cut-off point of 1 month as being optimal for intervention. However, they admit that there is currently no evidence for an effective screening programme to target those most at risk for long-term disability.…”
mentioning
confidence: 99%
“…Sixty to eighty percent of grown ups will sooner or later face health predicaments with low back pain (LBP) [6,7,8], and 16% of grown ups in the United Kingdom (UK) counsel their general specialist consistently [9]. Back pain costs the National Wellbeing Administration (NHS) £1.3 million consistently [10] which causes about 12.5% of all work nonattendance in the UK [11]. Due to that, the intercession to treat nonspecific constant low back pain (NSCLBP) stays tricky [12].…”
Section: Introductionmentioning
confidence: 99%